The effects of general anesthetics on mitochondrial structure and function in the developing brain - Hogarth, Kaley; Tarazi, Doorsa; Maynes, Jason T. (Frontiers in Neurology, 2023)
The use of general anesthetics in modern clinical practice is commonly regarded as safe for healthy individuals, but exposures at the extreme ends of the age spectrum have been linked to chronic cognitive impairments and persistent functional and structural alterations to the nervous system. The accumulation of evidence at both the epidemiological and experimental level prompted the addition of a warning label to inhaled anesthetics by the Food and Drug Administration cautioning their use in children under 3  years of age. Though the mechanism by which anesthetics may induce these detrimental changes remains to be fully elucidated, increasing evidence implicates mitochondria as a potential primary target of anesthetic damage, meditating many of the associated neurotoxic effects. Along with their commonly cited role in energy production via oxidative phosphorylation, mitochondria also play a central role in other critical cellular processes including calcium buffering, cell death pathways, and metabolite synthesis. In addition to meeting their immense energy demands, neurons are particularly dependent on the proper function and spatial organization of mitochondria to mediate specialized functions including neurotransmitter trafficking and release. Mitochondrial dependence is further highlighted in the developing brain, requiring spatiotemporally complex and metabolically expensive processes such as neurogenesis, synaptogenesis, and synaptic pruning, making the consequence of functional alterations potentially impactful. To this end, we explore and summarize the current mechanistic understanding of the effects of anesthetic exposure on mitochondria in the developing nervous system. We will specifically focus on the impact of anesthetic agents on mitochondrial dynamics, apoptosis, bioenergetics, stress pathways, and redox homeostasis. In addition, we will highlight critical knowledge gaps, pertinent challenges, and potential therapeutic targets warranting future exploration to guide mechanistic and outcomes research.